Better CRT Response in Patients Who Underwent Atrioventricular Node Ablation or Upgrade From Pacemaker: A Nomogram to Predict CRT Response - Xiao, Pei-Lin; Cai, Cheng; Zhang, Pei; Han, Jie; Mulpuru, Siva K.; Deshmukh, Abhishek J.; Yin, Yue-Hui; Cha, Yong-Mei (Frontiers in Cardiovascular Medicine, 2021)
Background: Response rates for cardiac resynchronization therapy (CRT) in patients without left bundle-branch block (LBBB) morphology are poor. Objective: We sought to develop a nomogram model to predict response to CRT in patients without LBBB. Methods: We searched electronic health records for patients without LBBB who underwent CRT at Mayo Clinic (2002-2017). Logistic regression and Cox proportional hazards regression analysis were performed for the odds of response to CRT and risk of death, respectively. Results were used to develop the nomogram model, which was then validated. Results: Among 761 patients identified, the mean (SD) age was 69 (12) years, and 79% were men. Six months after CRT, 47.8% of patients demonstrated improvement of left ventricular ejection fraction by more than 5%. The 1-, 3-, and 5-year survival rates were 95.9%, 82.4%, and 66.70%, respectively. Patients with CRT upgrade from pacemaker (odds ratio [OR], 1.67 [95% CI, 1.05-2.66]) or atrioventricular node (AVN) ablation (OR, 1.69 [95% CI, 1.09-2.64]) had a greater odds of CRT response. Patients with right bundle-branch block had a low response rate (39.2%). Patients undergoing AVN ablation had a lower mortality rate than those without ablation (hazard ratio, 0.65 [95% CI, 0.46-0.91]). Eight clinical variables were automatically selected to build a nomogram model and predict CRT response. The model had an area under the receiver operating characteristic curve of 0.71 (95% CI, 0.63-0.78). Conclusions: Among patients without LBBB undergoing CRT, upgrade from pacemaker and AVN ablation were favorable factors in achieving CRT response and better long-term outcomes.